Research on capacity configuration optimization of energy storage system participating in peak shaving. Issue 1 (1st February 2022) - Zhang, Fan; Mao, Cui; Zhou, Shan; Chen, Yuping; Wang, Yongli; Tian, Hankui; Yuan, Bo
Abstract: The "carbon double" goal calls for a further increase in the proportion of installed renewable energy capacity in China. The need to further expand the share of installed renewable energy capacity in China is increasing the need for ancillary peaking of the grid. There is also an ever-increasing need for peaking. The configuration of the energy storage system is one of the effective ways to reduce the peak load of each unit and increase the receiving space for renewable energy. Taking wind power generation as an example, the optimization model of thermal energy storage system is studied, the charging and discharging control strategy of energy storage system is designed, the integrated load impact on the grid due to wind power generation variation is considered, and the optimal economics and wind power generation are sought to maximize the comprehensive benefits.